Sliding Mode Controller Design Based on Pole Placement Method / Nor Laili Mahmud...[et al.] - Mahmud, Nor Laili; Mohd Arshad, Mohd Arshad; Adnan, Ramli (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
Over the years, many researchers have considered the problem of stabilizing uncertain systems. In variable structure control (VSC) system, the controller structure around the plant is intentionally changed by using a viable high-speed switching feedback control to obtain a desired plant behavior or response. In this paper, the problem of designing a VSC law for uncertain system, Electrohydraulic control system is considered. Using Pole Placement approach, an alternative design method of a linear sliding surface which is linear to the state is developed. A sufficient condition for the existence of linear sliding surface is given and an explicit formula of linear sliding surfaces guaranteeing the quadratic stability of the reduced-order equivalent system dynamics restricted to the sliding surfaces is derived. The sliding mode controller is then applied to an Electrohydraulic servo system. The simulation works were performed using MATLAB/SIMULINK software. A comparison for the controller design using Pole Placement Method with and without the sliding mode control shows that the Pole Placement method with a sliding mode control method produces a better performance response.